A Longitudinal Study of Gambling Behaviors During the COVID-19 Pandemic in Sweden - Månsson, Viktor; Wall, Håkan; Berman, Anne H.; Jayaram-Lindström, Nitya; Rosendahl, Ingvar (Frontiers in Psychology, 2021)
This study aimed to investigate changes in gambling behaviors during the first and second waves of the COVID-19 pandemic in Sweden. Participants who had gambled within the past year were recruited from social media and the Swedish National Helpline (n=325, mean age 39.8 years, 64.8% males, 31.3% with problem gambling) and completed an online survey measuring gambling behaviors, consequences of the pandemic in general and worries related to the pandemic. A sub-sample (n =139) completed a follow-up survey, during the second wave. The results showed no significant associations between COVID-19 consequences (financial or increased isolation) and increased monthly gambling behavior. No major migrations were observed between game types. However, gambling on a high-risk game (OR=7.44, p < 0.001) and worrying about mental health due to the pandemic (OR=2,85, p < 0.001) were significantly associated with past-year gambling problems and increased monthly gambling problems from the first to the second wave. More longitudinal research is needed in vulnerable populations, to fully understand the long-term consequences of the pandemic